Survei Pendapat Masyarakat Mengenai Aplikasi untuk Pencegahan dan Penanganan COVID-19 di Jabodetabek - Siska Siska; Dedi Nugroho; Rizky Farmasita B. (Publikasi Indonesia, 2022)
With the current development of science and technology, information about COVID-19 is easy to know, the public has an important role in efforts to control COVID-19 by implementing health protocols and disciplined behavior. This study aims to determine public opinion regarding contact tracing applications for the prevention and handling of COVID-19 in JABODETABEK and to find out public opinion regarding the expected features in the application for the prevention and handling of user-friendly COVID-19. This research is a quantitative descriptive type by filling out a comprehensive questionnaire to 400 people in the JABODETABEK area. The data analysis technique used descriptive statistical analysis with validity and reliability testing to measure the validity or validity of a questionnaire and to show the consistency of a questionnaire. The results of this study indicate that many people who do not know have not downloaded, and have not used mobile phone applications for the prevention and handling of COVID-19, but many people expect a contact tracing application equipped with user-friendly features, which can be a solution. Related to the prevention and handling of COVID-19 in JABODETABEK.